2014
DOI: 10.1145/2559936
|View full text |Cite
|
Sign up to set email alerts
|

Automated cookie collection testing

Abstract: Cookies are used by over 80% of Web applications utilizing dynamic Web application frameworks. Applications deploying cookies must be rigorously verified to ensure that the application is robust and secure. Given the intense time-to-market pressures faced by modern Web applications, testing strategies that are low cost and automatable are required. Automated Cookie Collection Testing (CCT) is presented, and is empirically demonstrated to be a low-cost and highly effective automated testing solution for modern … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 75 publications
0
8
0
Order By: Relevance
“…Ciupa et al (2008) have proposed a specific distance metric for object-oriented software. Tappenden and Miller (2013) have proposed a specific distance metric for cookies collection testing of web applications. It is understood that there are currently investigations into the application of ART in input domains involving strings, trees, finite state machines, etc.…”
Section: Various Art Algorithmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ciupa et al (2008) have proposed a specific distance metric for object-oriented software. Tappenden and Miller (2013) have proposed a specific distance metric for cookies collection testing of web applications. It is understood that there are currently investigations into the application of ART in input domains involving strings, trees, finite state machines, etc.…”
Section: Various Art Algorithmsmentioning
confidence: 99%
“…They have observed that ART was the best performer, but "there is a 9% probability of wrongly claiming that ART is better than RT if that is actually not the case" (Iqbal et al, 2011). Hemmati et al (2010Hemmati et al ( , 2011 have used ART to test a safety monitoring component of a safety-critical control system written in C++ and a core component of a videoconference system written in C. Tappenden and Miller (2013) have used Evolutionary ART in their cookie collection testing of six open-source web applications. Faults were detected in five out of the six web applications.…”
Section: Applications Of Art and Toolsmentioning
confidence: 99%
“…Cliff's δ was used in El-Attar (2014), El-Attar et al (2012) and Tappenden and Miller (2014). The probability of superiority metricP (referred to as 12 ) was used in Madeyski et al (2014) and Madeyski et al (2012).…”
Section: Arguments For the Use Of Robust Statisticsmentioning
confidence: 99%
“…For non-numeric inputs, the measurement should take account of the functionali- ties or characteristics of the SUT. Web applications, for example, often involve cookies, and Tappenden and Miller [31] proposed a cookie-based distance metric to evenly spread test inputs for web applications.…”
Section: B Adaptive Random Testingmentioning
confidence: 99%